2013
DOI: 10.1016/j.ajpath.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen-G Is Frequently Expressed in Glioblastoma and May Be Induced in Vitro by Combined 5-Aza-2′-Deoxycytidine and Interferon-γ Treatments

Abstract: Human leukocyte antigen-G (HLA-G) is a nonclassical major histocompatibility complex (MHC) class I molecule involved in immune tolerance processes, playing an important role in the maintenance of the semi-allogeneic fetus. Although HLA-G expression is restricted in normal tissues, it is broadly expressed in malignant tumors and may favor tumor immune escape. We analyzed HLA-G protein and mRNA expression in tumor samples from patients with glioblastoma collected in France, Denmark, and Brazil. We found HLA-G pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 63 publications
1
56
0
1
Order By: Relevance
“…Subsequent studies confirmed and extended this work to show that HLA-G is frequently expressed by primary GBM biopsies (65 out of 108 in one study). 36,37 These and other studies suggest that HLA-G expression by tumors is a mechanism for immune evasion.…”
Section: Natural Killer Cellsmentioning
confidence: 86%
“…Subsequent studies confirmed and extended this work to show that HLA-G is frequently expressed by primary GBM biopsies (65 out of 108 in one study). 36,37 These and other studies suggest that HLA-G expression by tumors is a mechanism for immune evasion.…”
Section: Natural Killer Cellsmentioning
confidence: 86%
“…Cell lines expressing HLA-G (JEG-3, FON) or not HLA-G (M8, U251MG) at the cell surface [36, 37] were cultured at 37°C under 5% CO 2 . The JEG-3 choriocarcinoma cell line (ATCC, Manassas, VA, USA) and the U251MG glioma cell line (provided by Dr. Heinz Wiendl, University of Münster) were cultivated in DMEM with Glutamax-I (Invitrogen, Cergy Pontoise, France).…”
Section: Methodsmentioning
confidence: 99%
“…Although downregulation of HLA class I reduces the immunogenicity of GBM cells, it could activate NK cell response against the tumor. However, GBM cells overexpress nonclassical HLA class I molecules, such as HLA-G and HLA-E 36, 37 , which are involved in the inhibition of NK and CTL responses to the allogeneic fetus during pregnancy. Changes in HLA class II expression have also been reported in GBM cells and have been associated with epigenetic changes in the class II transactivator (CIITA) promoter 38 .…”
Section: Introductionmentioning
confidence: 99%